Driving CARs to BARs: The Winding Road to Specific Regulatory T Cells for Tolerance - Scott, David W. (Frontiers in Immunology, 2021)
Chimeric antigen receptor (CAR) transduced T cells have significantly improved cancer immunotherapy. Similarly, engineering regulatory T cells (Treg) with specific receptors to endow specificity and increase efficacy of Tregs holds great promise for therapy of a variety of adverse immune responses. In this review, we focus on our approaches using retroviral transduction of specific T-cell receptors, single chain variable fragments (scFv) or antigen in models of monogenic diseases, autoimmunity and allergy. The advantages of each of these for different targets diseases are discussed as well as their potential for clinical translation.